PROPOSED STRATEGY OF USEETV TO INCREASE SUBSCRIBERS THROUGH ACQUISITION AND RETENTION: CASE STUDY AT PT. TELKOM INDONESIA - Neysa, Fredella
In 2019, Indonesia's pay-TV penetration was the lowest among APAC countries caused by competition with Free-to-Air and other pay-TV, signal piracy & unlicensed TV operators, and disruption from OTT youtube & SVOD such as Netflix. Nevertheless, Indonesia's pay-TV industry is still projected to grow from 5.9 to 6.9 million in 2019 to 2024.